THE CONTRIBUTION OF THE BELAWAN OCEAN FISHING PORT THE FISHERIES SECTOR OF NORTH SUMATERA PROVINCE - Retno Agus Haryani; Alit Hindri Yani; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAKThe purpose of this study was to know  the Contribution Of The Belawan Ocean Fishing Port to the Fisheries Sector Of  North Sumatera Province. By using  survey method, this research was conducted in May 2018. To find out the value of the contribution of the Belawan Ocean Fishing Port to The Fisheries Sector Of North Sumatera Province which was datermined by knowing the percentage (%), the fishing catch data on Belawan Ocean Fishing Port were compared with the fishing catch data in North Sumatera Province. Based on data from the Belawan Ocean Fishing Port and the North Sumatera Provincial Fisheries service from 2012-2016 shows that the role of the Belawan Ocean Fishing Port in the North Sumatera Province Fisheries Sector in terms of the number of Fishing Gear, Fishing Fleet, Number Of Fisherman, Fisheries Production, And Production Value as well as retribution is moderate because the contribution value is between 33,4% to 66.6% According to criteria (Siregar 2006).Keywords :Contribution, fishing port, fisheries sector.